MODEL PEMBELAJARAN IPS BERBASIS MASALAH INDUSTRI - Suwito Eko Pramono, Edi Kurniawan (Forum Ilmu Sosial, 2015)
The purpose of this study establish an Industry problem-based learning model in social studies at Junior High School. Method in this study is the method Research and development (R&D). Location of the study is the first Junior High School in Gebog Kudus district. The conclusions of this study states that (1) the learning social studies in junior Kudus is done by varying the lecture method, (2) implementation of the model constraint is due to the absence of a model that allows teachers to implement an integrated social studies learning , and (3) the learning models developed used as a viable alternative model of learning in social studies learning activities at school . Furthermore , it is advisable to conduct training for teachers to improve the quality of teachers in implementing the learning model is developed.